Inhibitory Activities of Griseofulvin and Its Analogues against Phytopathogenic Fungi - Zhu, Yu-Jing; Pan, Zhi-Zhen; Yu, Xiao-Jie; Li, Zhi-Cong; Su, Ming-Xing; Huang, Jian-Zhong; Wu, Song-Gang; Chen, Qing-Xi; Liu, Bo (Asian Journal of Chemistry, 2013)
The antifungal activity of griseofulvin was evaluated against phytopathogenic fungi including Fusarium moniliforme, Fusarium solani, Fusarium oxysporum and Colletotrichum truncatum. The greenhouse test was also made to evaluate the control efficiency of griseofulvin to eggplant powdery mildew. The results indicated griseofulvin could not only obviously inhibit fungi in laboratory experiments but efficiently control eggplant powdery mildew in greenhouse test. Subsequently, five griseofulvin analogues were synthesized and evaluated for antifungal activities against the four fungi. The results showed that these compounds performed significantly different activities in comparison with griseofulvin. The inhibition mechanism and bioavailability of active analogues were taken to expound their different performance and relations of structure and activity. The solubility in different solvents of analogues and griseofulvin was roughly evaluated and compared.